2018
DOI: 10.3389/fped.2017.00296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nasal Continuous Positive Airway Pressure and High-Flow Nasal Cannula on Sucking, Swallowing, and Breathing during Bottle-Feeding in Lambs

Abstract: The use of prolonged respiratory support under the form of high-flow nasal cannula (HFNC) or nasal continuous positive airway pressure (nCPAP) is frequent in newborn infants. Introduction of oral feeding under such nasal respiratory support is, however, highly controversial among neonatologists, due to the fear that it could disrupt sucking, swallowing, and breathing coordination and in turn induce cardiorespiratory events. The recent observation of tracheal aspirations during bottle-feeding in preterm infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
3
9
1
Order By: Relevance
“…Requirement for pulmonary support is a common rationale for delaying introduction of oral feeding and, ultimately, attainment of full oral feeding and hospital discharge, although the evidence supporting such delay is, at best, limited. There is animal work evaluating the safety of oral feeding during noninvasive positive-pressure support in lambs [12,13]. Samson and colleagues observed no increase in cardiorespiratory events during bottle feeding in full-term lambs on nasal CPAP or high-flow nasal cannula compared to lambs on no respiratory support [12].…”
Section: Discussionmentioning
confidence: 99%
“…Requirement for pulmonary support is a common rationale for delaying introduction of oral feeding and, ultimately, attainment of full oral feeding and hospital discharge, although the evidence supporting such delay is, at best, limited. There is animal work evaluating the safety of oral feeding during noninvasive positive-pressure support in lambs [12,13]. Samson and colleagues observed no increase in cardiorespiratory events during bottle feeding in full-term lambs on nasal CPAP or high-flow nasal cannula compared to lambs on no respiratory support [12].…”
Section: Discussionmentioning
confidence: 99%
“…A recent animal study not only provided evidence on safe bottle feeding and maintained sucking-swallowing-breathing coordination, but also on improved efficiency of bottle feeding in preterm and full-term lambs on nasal CPAP. 34,35 The same group of researchers showed that nasal CPAP seems to inhibit GER in newborn lambs by increasing the barrier function of the EGJ. 36 They believed that this was due to a decreased duration and depth of the transient relaxation of the LES.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Furthermore, NHF therapy facilitated swallowing of saliva even during respiratory management. [ 8 , 9 ] Terzi et al [ 16 ] reported the use of NIV for exacerbation of respiratory distress in patients with COPD, to secondarily reduce the frequency of swallowing during the inspiratory phase, and improve swallowing function. A study reported that aspiration is less likely to occur during NHF therapy than during NIV in both humans and animals.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that aspiration is less likely to occur during NHF therapy than during NIV in both humans and animals. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation